ISLAMIC LEGAL REVIEW OF THE DIVISION OF PROPERTY WHILE BOTH PARENTS ARE STILL ALIVE - Efdian Marbun (Journal of Golden Generation Multidisciplinary, 2025)
The reason for dividing inheritance while the heirs are still alive is to avoid conflicts that will give rise to conflicts between heirs and not contradict Islamic law. The provisions of the Compendium of Islamic Law regarding the distribution of inheritance to living heirs provide evidence that the condition of the testator's death remains an implicit condition for inheritance of his assets in the form of inheritance. However, the Compilation of Islamic Law provides another way to carry out the distribution of inheritance before the death of the heirs as stated in Article 187 paragraph (1) of the Compilation of Islamic Law. The Islamic legal view regarding the distribution of inheritance to living heirs can be taken if there is a risk of disputes and conflicts between heirs that result in losses.